The Role of Innovative Learning Environment in Improving Students’ Mathematics Learning Outcomes: A Systematic Review - Raden Nabilah Fahrani; Turmudi Turmudi; Jarnawi Afgani Dahlan (Gagasan Pendidikan Indonesia, 2023)
A good mathematics learning outcome can reflect a good quality of Education. However, factual conditions about Indonesian students' mathematics learning outcomes still need to be more hopeful. Because of that, this systematic review aims to analyze previous studies about the role of innovative learning environment (ILE) in increasing students' mathematics learning outcomes as a beginning step for increasing Indonesian students' mathematics learning outcomes. To reach the objective, we defined inclusion and exclusion criteria to collect articles from other countries about ILE in mathematics over the last six years, from 2018 to 2023, using Google Scholar. After that, we systematically analyzed the selected articles and described them in a three-point discussion to answer research questions, namely: (1) The definition and characteristics of ILE; (2) The definition of mathematics learning outcomes which developed through ILE; and (3) The role of ILE in increased students' mathematics learning outcomes. The result showed that ILE was proven to play a role in improving student mathematics learning outcomes, and results were best when learning focused on collaborative aspects. Thus, applying ILE can be one solution to fix the low students' mathematics learning outcomes.